Asynchronous Engagement through Online Discussion Forums: Experiences from English Language Students in a Philippine State University - Joseph Pascua Nacionales (Journal of English Language Studies, 2023)
The creation of a well-developed ecological environment for English language teachers in digital platforms is a relevant and humane practice amidst the pandemic. During these times of crisis, Higher Education Institutions (HEIs) in the Philippines need to adopt new learning modalities. However, some students find it difficult to attend in synchronous mode of classes, as an alternative way, teachers need to employ asynchronous activities such as conducting online discussion forums (ODFs) where students can freely interact and share their insights on a topic within the given timeframe. Studies conducted on ODFs in the English language classrooms remain scant, especially in the Philippines, which examined the same or related focus. Thus, through qualitative approach, semi-structured interviews were conducted to 21 freshmen English language students in a Philippine state university. Further, the data was analyzed using conventional content analysis method (Hsieh and Shannon, 2005). The findings indicated the students’ insights on the use of ODFs such as it its risk for cheating during the asynchronous forums, its accessibility through Facebook as a platform for asynchronous engagement, encourage the exchange of ideas for new learning opportunities, and helps review the previous lessons discussed. There were notable challenges encountered by the students, however, specific strategies they have employed were disclosed. Also, when ODFs will be managed well by classroom teachers, students will become more engaged in asynchronous discussions.